Structural And Reliability Analysis Of Solder Joint Under Vibration Loading - Chek, Muhammad Asyraf Wan (Universiti Sains Malaysia, 2019)
Most of the devices nowadays contained electronic parts and often operated in a vibration environment for extended periods without failing. The role of solder in electronic packages has expanded and act as electrical interconnection as well as mechanical bond to certain parts while the joint decrease in size and cost. Hence, it is essential to investigate the structure of the solder joint and its reliability under vibration loading. Models were simulated in structural analysis to simulate pull strength test to learn the structure and its strength while under random vibration to learn its behaviour and dynamic response under certain random excitation frequency. Models were subjected to Y-axis displacement loading in structural analysis where as in random vibration analysis, the models are exposed to frequency range of 3 Hz to 500 Hz. Result from structural analysis shows that the structure of solder joint affects the strength of interconnection between circuit pad and LED joint. Higher number of adhesives able provide more strength to the structure. All parts of the CAD model were excited from the exposed frequency and failure occurred at some parts of the model.